2007
DOI: 10.1055/s-2007-984486
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Cranial Fossa Gangliogliomas

Abstract: Ganglioglioma (GG) is an uncommon primary lesion of the central nervous system that is typically located supratentorially. There are only a few reports of GG arising from the cerebellum. To the best of our knowledge this is the first case of a cerebellar GG with supratentorial extension and a longstanding history before its recognition. In fact, this 29-year-old male presented with an 11-year history of intermittent headaches. A cranial computerized tomography (CT) performed at the onset of his complaints fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Alternatively, some gangliogliomas do not demonstrate gadolinium enhancement on MRI (Im et al 2002a). Less common locations in the optic nerve, chiasm and tract (Bergin et al 1988;Chilton et al 1990;Sugiyama et al 1992), hypothalamus (Liu et al 1996), trigeminal nerve (Athale et al 1999), brainstem (Garcia et al 1984;Davidson et al 1992), cerebellum (Mizuno et al 1987;Safavi-Abbasi et al 2007), thalamus (Johnson et al 2001), pineal gland (Hunt & Johnson 1989Johnson et al 1995) and spinal cord (Johannsson et al 1981) have been reported. In one report, for example, MRI was able to demonstrate leptomeningeal and subarachnoid spread along the middle cerebral artery and right Sylvian fissure in a patient with leptomeningeal metastasis (Tien et al 1992).…”
Section: Ganglioglioma Demographicsmentioning
confidence: 99%
“…Alternatively, some gangliogliomas do not demonstrate gadolinium enhancement on MRI (Im et al 2002a). Less common locations in the optic nerve, chiasm and tract (Bergin et al 1988;Chilton et al 1990;Sugiyama et al 1992), hypothalamus (Liu et al 1996), trigeminal nerve (Athale et al 1999), brainstem (Garcia et al 1984;Davidson et al 1992), cerebellum (Mizuno et al 1987;Safavi-Abbasi et al 2007), thalamus (Johnson et al 2001), pineal gland (Hunt & Johnson 1989Johnson et al 1995) and spinal cord (Johannsson et al 1981) have been reported. In one report, for example, MRI was able to demonstrate leptomeningeal and subarachnoid spread along the middle cerebral artery and right Sylvian fissure in a patient with leptomeningeal metastasis (Tien et al 1992).…”
Section: Ganglioglioma Demographicsmentioning
confidence: 99%
“…However, the enhancement pattern of the ganglioglioma may mimic a vascular malformation, and catheter angiography is required to exclude a vascular malformation. Intraoperatively, these tumors have in fact been found to be extremely vascular [35,37]. In this case, the numerous telangiectatic vessels (resembling an angioma) seen bordering the hematoma may have been responsible for the hemorrhage.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, epilepsy of cerebellar origin has also been reported in patients with cerebellar gangliogliomas [3,12,18,19,20]. In general, cerebellar gangliogliomas are rare, with only 30 cases being reported in the literature [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,31,32,33,34], and they usually present with a short history (mean 1.6 years) [35]. To our knowledge, this is the first documented case of a cerebellar ganglioglioma presenting with hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification and cystic components are inconsistently present. Histologically, GGs are characterized by both ganglion and glial cell components, with the latter determining how aggressive the tumor behaves [19] . These elements stain positive for the neural markers chromogranin, synaptophysin, and glial fibrillary acidic protein.…”
Section: Discussionmentioning
confidence: 99%